Glassomer—Processing Fused Silica Glass Like a Polymer. Issue 22 (2nd April 2018) - Kotz, Frederik; Schneider, Norbert; Striegel, Andreas; Wolfschläger, Andre; Keller, Nico; Worgull, Matthias; Bauer, Werner; Schild, Dieter; Milich, Marcel; Greiner, Christian; Helmer, Dorothea; Rapp, Bastian E.
Abstract: Fused silica glass is one of the most important high‐performance materials for scientific research, industry, and society. However due to its high chemical and thermal resistance as well as high hardness, fused silica glass is notoriously difficult to structure. This work introduces Glassomer, a solid nanocomposite, which can be structured using polymer molding and subtractive technologies at submicrometer resolution. After polymer processing Glassomer is turned into optical grade fused silica glass during a final heat treatment. The resulting glass has the same optical transparency as commercial fused silica and a smooth surface with a roughness of a few nanometers. This work makes high‐performance fused silica glass components accessible to high‐throughput fabrication technologies and will enable numerous optical, photonic and medical applications in science and industry. Abstract : Glassomer is a solid silica nanocomposite that can be structured and processed like a polymer and sintered to full‐density transparent fused silica glass. Processing of Glassomer can be done using standard polymer processing equipment including lathing, milling, drilling, cutting, and carving, as well as thermal nanoimprinting and roll‐to‐roll replication.